2014
DOI: 10.1111/febs.13121
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐specific nuclease activity of RAGs is modulated by sequence, length and phase position of flanking double‐stranded DNA

Abstract: RAGs (recombination activating genes) are responsible for the generation of antigen receptor diversity through the process of combinatorial joining of different V (variable), D (diversity) and J (joining) gene segments. In addition to its physiological property, wherein RAG functions as a sequence-specific nuclease, it can also act as a structure-specific nuclease leading to genomic instability and cancer. In the present study, we investigate the factors that regulate RAG cleavage on non-B DNA structures. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…41 The protein was purified as described previously. 53, 54, 55 In brief, HEK 293 T cells were transfected with plasmid constructs using Calcium phosphate method. Cells were harvested after 48 h of transfection, protein lysate was prepared and RAG proteins were purified using amylose resin column chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The protein was purified as described previously. 53, 54, 55 In brief, HEK 293 T cells were transfected with plasmid constructs using Calcium phosphate method. Cells were harvested after 48 h of transfection, protein lysate was prepared and RAG proteins were purified using amylose resin column chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…53, 54, 57 In brief, appropriate [γ- 32 P] ATP-labelled oligomeric DNA substrates were incubated with RAG proteins (100 ng) in a buffer containing 22.5 mM MOPS-KOH (pH 7.0), 20% DMSO, 2.2 mM DTT, 50 mM potassium glutamate, 2% (v/v) glycerol and 100 ng/ml BSA for 2 h at 25 °C following which fixation was carried out (0.01% v/v gluteraldehyde at 37 °C for 10 min). The DNA–protein complexes were allowed to form in the presence of 5 mM CaCl 2 and increasing concentration of integrase inhibitors (0, 0.1, 0.2, 0.3 and 0.5 mM) and resolved on native polyacrylamide gels (6%).…”
Section: Methodsmentioning
confidence: 99%
“…Oligomeric DNA, obtained from Macrogen (Seoul, South Korea) was purified as described earlier. 27 Refer the Supporting Information for a sequence of oligomers used in the study.…”
Section: Oligomeric Dna Substratementioning
confidence: 99%
“…). However, recent studies showed that the sequence of both the single‐stranded region of the non‐B‐DNA and its flanking DNA sequences may regulate RAG cleavage at such structures . On cleavage, signal joints are formed that may be insert at a target site due to the transposase activity of RAGs .…”
Section: Role Of the Dna Sequence In Chromosome Fragilitymentioning
confidence: 99%